Principles of Formation of Complex Strategies: An Approach Based On the Theory of Complexity - Díaz Rojas, Carlos Andrés (2023)
This research applies complexity theory to explain the formation process of complex strategies. A systematic literature review was carried out to identify the state of the art and it was observed that the theoretical framework of the theory is dispersed. In this context, the local behavior scheme, unpredictability, self-organization, emergent order and evolution on the edge of chaos were identified as the most representative constructs of the theory. Based on these concepts, it was concluded that managers have a fundamental role in leading organizations; that strategies must promote experimentation, improvisation, trial and error; and that they must be constantly updated based on changes in the environment. Finally, a conceptual model of the complex strategy formation process is developed and a set of practical recommendations is provided.